Rancang Bangun Alat Peraga Up Lock Box Pada Nose Landing Gear Pesawat ATR 72 Untuk Media Pembelajaran - Septian, Diaz; Arifin, Mufti; Yuniarti, Endah (Jurnal Teknologi Kedirgantaraan, 2022)
Abstract - Airplane is a very important mode of transportation, one of which is ATR aircraft. In this study, the type of aircraft used was the ATR 72-600 aircraft. One of the safety factors that need to be considered on aircraft is the landing gear system. The landing gear system regulates the wheel system on the aircraft for landing and also taking off. Given the importance of ensuring that the plane's wheels are securely locked or not, an up lock box system is needed on the landing gear. In the Up Lock Box system, it is not directly visible from the outside so that the working mechanism is not widely known. This study aims to determine the workings of the up lock box nose teaching aid system on the landing gear and to make a trial up lock box nose teaching aid on the landing gear. The research method begins with a literature study, then looks for design references, namely from the ATA 32 training manual. After that, make a design using the image of the up lock box from the ATR 72 aircraft, assemble the demonstran tool, calibrate and test the demonstran tool. The conclusions in this study are, how the up lock box teaching aids work in accordance with the up lock box working concept in the training manual, the results of the design and manufacture of props accompanied by modifications, as well as the test results on up lock box props in accordance with the up lock work concept box. The size of the props that have been made has a length of 37.8 cm and a width of 16.2 cm.